2017
DOI: 10.5004/dwt.2017.21612
|View full text |Cite
|
Sign up to set email alerts
|

Chitosan anchored zinc oxide nanocomposite as modified electrochemical sensor for the detection of Cd(II) ions

Abstract: a b s t r a c tThe chitosan anchored zinc oxide nanocomposite (NC) has been prepared using chemical approach. The obtained NC was used as modified electrode for selective detection of Cd(II) ions using square wave voltammetry under pH 6 phosphate buffer solution. Surface area and porous nature of NC were found by using Brunauer-Emmett-Teller isotherm analysis. The presence of functional groups was confirmed using Fourier transform infrared spectroscopic analysis. The results indicated that detection starts at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…2 b cellulose templated extract mediated CuS NPs depicts the lower crystallinity with decreased crystallite size. The size of the crystallite was found to be in the range of 24.3–9.7 nm which was calculated Debye‐Scherrer formula [14]. A careful examination of XRD spectrum of extract mediated CuS NPs reveals that intensities of diffraction peaks were lower than non‐extract mediated CuS NPs.…”
Section: Resultsmentioning
confidence: 93%
“…2 b cellulose templated extract mediated CuS NPs depicts the lower crystallinity with decreased crystallite size. The size of the crystallite was found to be in the range of 24.3–9.7 nm which was calculated Debye‐Scherrer formula [14]. A careful examination of XRD spectrum of extract mediated CuS NPs reveals that intensities of diffraction peaks were lower than non‐extract mediated CuS NPs.…”
Section: Resultsmentioning
confidence: 93%
“…In this research work, the preparation of graphene oxide (GO) was performed as reported earlier, using a modified Hummer’s method. Previously, ZnO has been prepared using wet chemical method, which was reported earlier in our works. , In this work, the process for rapidly growing ZnO nanorods is developed using a hydrothermal technique and was described in the following section. To prepare ZnO/FTO electrode, substrate 2 (FTO) was dip-coated with ZnO sol to obtain a seed layer, using 0.05 M zinc acetate in ethanol.…”
Section: Experimental Methodsmentioning
confidence: 99%
“…In a recent article, we described the procedure for making CeO 2 nano-particles and CeO 2 /GO hybrid nanocomposite (28). ZnO nanoparticle was prepared by using simple wet chemical route in which 1.2 g of Zinc acetate dihydrate was stirred along with 0.4 g of sodium hydroxide (41). Further, 1 g of CeO 2 NPs powder was diluted in 100 ml distilled water and ultrasonically processed for 30 minutes.…”
Section: Preparation Of Ceo 2 /Zno/go Hybrid Nanocompositementioning
confidence: 99%